The effects of patellar tendon vibration on quadriceps strength in anterior cruciate ligament reconstructed knees. (November 2019) - Goetschius, John; Hertel, Jay; Saliba, Susan; Brockmeier, Stephen F.; Hart, Joseph M.
Abstract: Objectives: To examine the immediate effects of prolonged patellar tendon vibration on quadriceps strength in anterior cruciate ligament reconstructed (ACLR) knees with bone-patellar tendon-bone (BTB) grafts and non-BTB grafts, and healthy control knees. Design: Pretest-posttest design. Setting: Laboratory. Participants: Young adult participants were stratified into one of three groups: non-BTB graft (n = 25), BTB graft (n = 26), and controls without ACLR (n = 21). Main outcome measures: Maximum voluntary isometric contraction (MVIC) knee extension torque was measured at baseline and following a 20-min vibration intervention applied locally to the patellar tendon. Results: Our findings suggest there was no difference in the effects of vibration on knee extension torque between the three groups. Knee extension torque significantly increased (effect size = 0.52 [0.18 to 0.81]) from baseline to post-vibration across all three groups (0.30 ± 0.26 Nm/kg, 21.8 ± 20.0%). Both ACLR groups demonstrated significantly lower knee extension torque compared the control group. Conclusions: The vibration intervention had a net excitatory effect on quadriceps strength in all three groups and there were no differences in the magnitude of change between the three groups. Vibration could become a useful tool for enhancing quadriceps strength in ACLR and healthy knees. Highlights: Quadriceps strength improved in ACLR and healthy knees after vibration intervention. Improvements in quadriceps strength were similar between graft types and controls. Vibration may provide opportunity to enhance quadriceps function in ACLR knees.